2023
DOI: 10.3390/toxins15070426
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of Deoxynivalenol in Dezhou Male Donkeys after Oral Administration

Abstract: Deoxynivalenol (DON) is detected in different types of foods and feeds, inducing toxicity in humans and animals. After entering the organism, DON first appears in the plasma; then, it is rapidly absorbed and distributed in various organs and tends to accumulate in the body to exert its toxic effects. This study was performed to investigate the toxicokinetics of DON on Dezhou male donkeys after a single oral dose of 500 μg/kg·BW (body weight). The plasma of donkeys was collected at 0, 5, 10, 15, 20, 30, 45 min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…In recent years, with the modernization of agriculture, donkeys have emerged as multi-purpose farm creatures in some countries, such as companion animals, and even dairy or meat-producing animals [ 30 ]. Our previous toxicokinetics research of ochratoxin and deoxynivalenol in donkeys showed the absorption, elimination, and excretion parameters of both toxins in donkeys were different from other animals [ 31 , 32 ]. However, there is no research to be found about the toxicokinetics of ZEN in donkeys.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the modernization of agriculture, donkeys have emerged as multi-purpose farm creatures in some countries, such as companion animals, and even dairy or meat-producing animals [ 30 ]. Our previous toxicokinetics research of ochratoxin and deoxynivalenol in donkeys showed the absorption, elimination, and excretion parameters of both toxins in donkeys were different from other animals [ 31 , 32 ]. However, there is no research to be found about the toxicokinetics of ZEN in donkeys.…”
Section: Introductionmentioning
confidence: 99%